Changes dynamics in the cornea layers of the rat eye at the end of the fourth week of experimental streptozocin diabetes - Rudnytska , Kh.I.; Servetnyk , M.I.; Ambarova , N.O.; Simonov , V.F.; Hrytsenko , A.P.; Tverdokhlib , I.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. Ophthalmic complications of diabetes are still a huge medical and social problem worldwide. Taking into account the above, diabetic damage to the structures of the eyeball will continue to be an actual problem of the possible development of diabetic damage to the cornea. The aim of our study was to find out the features of the microstructural reconstruction of the rat cornea at the end of the fourth week of experimental streptozotocin-induced diabetes. Methods. Experimental diabetes was induced by a single intraperitoneal injection of streptozotocin at the rate of 7 mg per 100 g of body weight. Research was conducted from the fourth week of the experiment on animals with a glucose level of more than 15.58 mmol per 1 liter. 2 groups of animals were used in the work: 1 group (10 animals) with diabetes that developed (4 weeks after administration of streptozotocin); Group 2 was the control group (5 animals). Preparations for histological examination were prepared according to generally accepted methods. Microscopic studies and photography of the preparations were carried out using a MBI-1 microscope and a Nicon D 3100 digital camera. Results and conclusion. The outer epithelium was preserved in most areas, but alterative changes were registered in the cells of the basal, middle and superficial layers. The cells of the basal layer were located loosely. Epitheliocytes with vacuolated cytoplasm and compacted, homogeneously basophilic, pyknotic nucleus were found in the basal layer. Cells of the middle and superficial layers of the outer epithelium of the cornea were randomly arranged chaotically. Epitheliocytes with vacuolated cytoplasm were also found in these layers. As a result of dystrophic and necrotic changes in the cells of the basal and middle layers, there were foci of destructively changed epithelial cells in the layer of the outer epithelium of the cornea. In addition, in the back part of the corneal stroma, the matrix was unevenly colored, in separate plates it had a fine-grained acidophilic appearance. Keratocytes were located sparsely. Areas of edema also occurred between the connective tissue plates of the corneal stroma and Descemet's membrane. The endothelium of the anterior chamber of the eye was detached from Descemet's membrane in some areas. There were areas of corneal bulging where a decrease in the number of rows of cells in the middle and superficial layers was noted. Between the connective tissue plates of the corneal stroma and the Descemet's membrane, there were also areas of edema with detachment of the endothelium of the anterior chamber from the Descemet's membrane. The study of the structural rearrangement in the layers of the cornea at the end of the fourth week of experimental streptozotocin-induced diabetes will provide an opportunity to compare the depth of pathomorphological changes at different time points, which will further contribute to the creation of a pathomorphological basis for establishing the optimal terms from the point of view of morphology for drug correction of changes in the layers of the cornea in subchronic terms of exposure hyperglycemia in order to stabilize the emerging and subsequently progressing phenomena of diabetic keratitis.